Characterization of four states polarization flipper for single photon application - Abdul Khir , Mohd Fared; Mohd Zain, Mohd Norzaliman; , Suryadi; Saharudin, Suhairi; Shaari, Sahbudin (2010)
We report characterization result using weak coherent pulses on four states polarization flipper utilizing two Pockels cells. Visibility of nearly 90 and above was achieved for each four linear polarization input states. A good polarization contrast between not flipped and flipped states shows that this configuration can be applied for single photon applications.